Rethinking Streets: Enhancing Public Spaces and Pedestrian Amenities in Liverpool, Sydney - Awais Saeed, Agha (INTI International University, 2024)
This paper undertakes an analysis and provides strategic design recommendations to urbanise Liverpool City Centre, Sydney; by proposing the conversion of the existing fragmented car oriented space into one that is inclusive, pedestrian orientated public domain. Those include problems with car monopolisation and lack of facilities for pedestrians and cyclists, the "Rethinking Streets" project noted. The Complete Street project designs streets for all users, with four modes of transportation accommodated in the same right-of-way. In theory, measures like extending the pedestrian sphere, facilitating linear bike connections and updating streetscape elements as well as parking removal to ease through-traffic could be considered. These enhancements aim to promote a healthier environment, improve connectivity among major attractions, and support economic growth, aligning with Liverpool's vision as a regional hub in Sydney's Metropolitan Plan